Heterogeneous Manganese‐Catalyzed Oxidase C−H/C−O Cyclization to Access Pharmaceutically Active Compounds. Issue 2 (27th November 2019) - Ferlin, Francesco; Marini, Alberto; Ascani, Nicola; Ackermann, Lutz; Lanari, Daniela; Vaccaro, Luigi
Abstract: Heterogeneous manganese‐catalyzed C−H oxidative couplings were accomplished to gain access to pharmaceutically relevant 2‐aminophenoxazin‐3‐ones and to diaminophenazine and purpurogallin moieties in excellent yields. The user‐friendly K‐OMS‐2 oxidase strategy proved to be more versatile and robust than enzymatic catalysts‐based procedures allowing a wider substrate scope and being effectively reusable as proven by leaching measurements and XRD analyses. Abstract : Mimicking peroxidase : Heterogeneous Mn‐catalyzed C−H oxidative couplings were accomplished to access pharmaceutically relevant phenoxazinones. The user‐friendly K‐OMS‐2 oxidase strategy proved to be more versatile and stable than enzymatic catalysts opening to a wider substrate scope and being effectively reusable as proven by leaching measurements and XRD analyses.